Sexual Desire and Hormonal Contraception. Issue 3 (March 2016) - Boozalis, Amanda; Tutlam, Nhial T.; Chrisman Robbins, Camaryn; Peipert, Jeffrey F.
Abstract : OBJECTIVE: To examine the effect of hormonal contraception on sexual desire. MATERIALS AND METHODS: We performed a cross-sectional analysis of 1, 938 of the 9, 256 participants enrolled in the Contraceptive CHOICE Project. This subset included participants enrolled between April and September 2011 who completed a baseline and 6-month telephone survey. Multivariable logistic regression was used to assess the association between contraceptive method and report of lacking interest in sex controlling for potential confounding variables. RESULTS: More than 1 in 5 participants (23.9%) reported lacking interest in sex at 6 months after initiating a new contraceptive method. Of 262 copper intrauterine device (IUD) users (referent group), 18.3% reported lacking interest in sex. Our primary outcome was more prevalent in women who were young (younger than 18 years: adjusted odds ratio [OR] 2.04), black (adjusted OR 1.78), and married or living with a partner (adjusted OR 1.82). Compared with copper IUD users, participants using depot medroxyprogesterone (adjusted OR 2.61, 95% confidence interval [CI] 1.47–4.61), the vaginal ring (adjusted OR 2.53, 95% CI 1.37–4.69), and the implant (adjusted OR 1.60, 95% CI 1.03–2.49) more commonly reported lack of interest in sex. We found no association between use of the hormonal IUD, oral contraceptive pill, and patch and lack of interest in sex. CONCLUSION: CHOICE participants using depot medroxyprogesterone acetate, the contraceptive ring, and implant were more likely to report a lack of interest in sex compared with copper IUD users. Future research should confirm these findings and their possible physiologic basis. Clinicians should be reassured that most women do not experience a reduced sex drive with the use of most contraceptive methods. Abstract : Compared with copper intrauterine device users, women using depot medroxyprogesterone injection, the ring, and the implant were more likely to report lack of interest in sex.